Anri Sala: Altered Times and Spaces - Simó Mulet, Toni; Segura Cabañero, Jesús (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
In this text we will analyse the work of Anri Sala. Her audiovisual installations use film and video-based media, altering the concepts of space and time. In the first section, we propose the work Time after Time (2003) where she breaks time and space and introduces the idea of the disruption of everyday life as a time of experience. In a second section, we will deal with the work Ravel, Ravel, Unravel (2013) in which we discuss the manipulations of time and space. And we will conclude, as Anri Sala invokes in her work both the emotion and the body of the Viewer.